Paradox between agricultural production and food insecurity (Interdisciplinary Studies Journal, 2024)
This article discusses the paradox between significant agricultural production and the situation of food insecurity in Brazil. To this end, scientific articles and research data from national bodies were used in a quantitative, qualitative and exploratory way. The data showed that in 2022 the total cultivated area was 63.6 million ha, resulting in 312.4 million tons produced. On the other hand, 28% of the Brazilian population was at a mild level on the food insecurity scale, 15.2% at a moderate level and 15.5% at the most severe level, with the majority of the population going hungry at this stage. This worsening is due to the weakening of public policies and factors related to poor management of food production. We can see that the adequate management of public policies with the aim of ensuring the right to food security directly influences the improvement of these indicators, together with the strengthening of family and rural agriculture.
Keywords: Hunger; Social inequality; Public policies